GE_GERICHTE C/8256/2016 vom 1. Oktober 2018 - GE Cour de justice (2018)
FORMULE OFFICIELLE ; CALCUL; RENDEMENT BRUT ; MOTIVATION DE LA DÉCISION ; INTÉRÊT MORATOIRE | OBLF.19; CO.270.al1; CO.269; Cst.29.al2; CO.104.al1; CO.102.al1